Factors associated with energy intake among adolescents in selected secondary schools in Hulu Langat district, Malaysia - Mohd Shahar, Aainaa Syarfa (2015)
This cross-sectional study aimed to determine factors associated with energy intake among adolescents in Hulu Langat district. Multistage cluster sampling was used for school and class selection. One class was selected from each form 1, form 2 and form 4 classes within each school by the principal. Anthropometric measurements such as height, body weight and waist circumference were taken. Respondents completed questionnaires consisted of socio-demographic background, lifestyle practices (eating behaviours, physical activity, smoking habits and sleeping hours), personality traits, parenting styles, social support and dietary intake. Eating behaviours were assessed using Three-Factor Eating Questionnaire-R18. Physical Activity Questionnaire for Adolescents (PAQ-A), WHO Global School-Based Student Health Survey Model (GSHS) and formula of (mean hours of sleeping on weekdays x 5) + (mean hours of sleeping on weekends x 2) / 7 for average hours (and minutes) of sleep during weekdays and weekend days were used to determine physical activity, smoking habits and sleeping hours respectively. Personality traits were obtained using USM Personality Inventory (USMaP-i). Parenting styles were assessed through Parental Authority Questionnaire, while social support was determined using Multidimensional Scale of Perceived Social Support (MSPSS). The current dietary intake was measured through 24-hour dietary recall. Altogether, there were 199 male and 231 female students from five randomly selected schools participated in this study on a voluntary basis. The sample comprised of 84.7% Malays, 7.9% Chinese, 6.7% Indian, while 0.7% were from other ethnic groups. Distribution of the respondents according to age showed 29.1% aged 13 years old, while 34.7% and 36.3% aged 14 and 16 respectively. A majority of the respondents’ father (91.4%) and mother (92.3%) aged between 36 - 55 years old with the mean age of 46.45 ± 5.67 and 43.34 ± 5.39 for father and mother respectively. Most of the parents had at least finished secondary school with a proportion of 50.0% and 57.2% for respondents’ father and mother respectively. More than half of the respondents’ mother (67.2%) has a total income below RM 2300 with a median of RM 800.00, while most of the respondents’ fathers (49.1%) earn between RM 2300 - RM 5599 with a mean of RM 3720.62 ± 2792.83. Uncontrolled eating is the most prevalent among respondents with female respondents significantly having a higher score of restrained eating (t=-2.477, p<0.05) and emotional eating (t=-2.089, p<0.05) compared to male respondents. In contrast, male respondents reported to score higher than female respondents for physical activity part (t=5.756 p<0.01). Current smoking was reported by 3.0% of the respondents. Sleeping duration of the respondents was longer during weekdays than weekend days with female respondents reported having longer sleeping hours (8.43 ± 7.30) during the weekend, as compared to male respondents who tend to sleep longer during weekdays (7.79 ± 5.10). Female respondents were more likely to be neurotic (t=-4.961, p<0.01) and agreeable (t=-4.961, p=<0.01) as compared to male respondents. Both of father (t=3.189, p<0.01) and mother (t=3.443, p<0.01) were more permissive towards males compared to females, while mother authoritativeness was significantly greater among females (t=-2.604, p<0.01). The respondents relied more on family members and friends as the main support. A proportion of 31.2% and 22.9% were in the overweight and obese category for male and female respondents respectively. Mean of BMI-for-age for male and female respondents was 0.17 ± 1.52 and 0.55 ± 1.34 respectively. Waist circumference showed that around 21.6% of female and 15.6% of male respondents had a high risk of developing abdominal obesity with a mean of 72.16 ± 11.85cm in males and 73.08 ± 10.06cm in females. The consumption of energy, protein and several key micronutrients did not meet Recommended Nutrient Intake (RNI). Males significantly have a higher intake of energy with a mean of 1425 ± 583 kcal compared to females with a mean of 1232 ± 529 kcal. Prevalence of misreporting of energy intake was high with 79.6% of them were underreported and 2.4% over reported. Respondents with a higher score of uncontrolled eating (r=0.231, p<0.01), highly perceived their fathers (r=0.107, p<0.05) and mothers (r=0.104, p<0.01) as authoritarian, highly perceived their fathers (r=0.098, p<0.05) and mothers as permissive (r=0.098, p<0.05), have high supportive family (r=0.142, p<0.05) and friends (r=0.095, p<0.05) were found to be significantly associated with higher energy intake. On the other hand, higher energy intake was associated among respondents with low conscientiousness trait (r=-0.158, p<0.01), low BMI-for-age (r=-0.147, p<0.01) and smaller waist circumference (r=-0.108, p<0.05). Uncontrolled eating (beta=0.090, p<0.05) was found to have the strongest influence on energy intake of the respondents and followed by conscientiousness trait (beta=-0.068, p<0.05). The findings of this study showed that energy consumption of adolescents could be influenced by lifestyle and individual trait. This is in line with the findings of previous studies in which uncontrolled eating style may result in overconsumption of food. Personality traits often associated with human behaviours with low conscientious individuals consumed more energy compared to high conscientious individuals. Findings on their lifestyle practices and nutritional status indicate a need for a healthy lifestyle intervention program in future. Both of individual and interpersonal factors should be considered when planning and implementing future intervention with specifically focusing on self-regulation of eating and personality-based approach.